Laminated composite current collector soft package pole group and battery

By using L-shaped ear stacks of different lengths to weld with aluminum foil or copper foil in the laminated composite fluid-collection soft-coated electrode group, the problem of excessive thickness at the welding of traditional battery ears is solved, and the multi-layer conduction and safety performance are improved.

CN222619775UActive Publication Date: 2025-03-14JIANGSU HIGHSTAR BATTERY MFG CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202421012649.0
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-05-10
Publication Date
2025-03-14
Estimated Expiration
2034-05-10

AI Technical Summary

Technical Problem

Traditional laminated lithium-ion batteries are too thick at the electrode welding point, making it difficult to be suitable for laminated soft-pack batteries with high space requirements.

Method used

Using a laminated composite fluid-collection soft-coated electrode group, a plurality of positive electrode ears and negative electrode ears of different lengths are flattened in the thickness direction of the superimposed body to form an L-shaped electrode ear overlap, and weld it with aluminum foil or copper foil, multi-layer conduction is achieved and the thickness at the electrode weld is reduced.

Benefits of technology

Multi-layer conduction of composite foil is achieved, the thickness of the electrode welding is reduced, and the energy density and safety performance of lithium-ion batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222619775U_ABST
    Figure CN222619775U_ABST
Patent Text Reader

Abstract

The utility model relates to the technical field of battery process manufacturing, and discloses a laminated composite current collector soft package pole group and a battery, the laminated composite current collector soft package pole group comprises a laminated body formed by alternately laminating a plurality of positive plates and a plurality of negative plates, the lengths of the positive tabs of the plurality of positive plates are gradually increased or gradually reduced, and the lengths of the negative tabs of the plurality of negative plates are gradually increased or gradually reduced; the positive plate takes a composite aluminum foil as a base material, and the negative plate takes a composite copper foil as a base material; a plurality of positive tabs with different lengths are flattened along the thickness direction of the lamination body to form an L-shaped positive tab lamination body, and a plurality of negative tabs with different lengths are flattened along the thickness direction of the lamination body to form an L-shaped negative tab lamination body; and the L-shaped positive tab overlapping body is welded with the aluminum foil, and the L-shaped negative tab overlapping body is welded with the copper foil. According to the laminated battery, the problem that a plurality of layers of tabs are welded too thick when the laminated battery is prepared by taking a composite foil as a base material is solved, and the laminated battery has a wide practical application scene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the technical field of battery manufacturing process, in particular to a laminated composite current collector soft-package electrode group and a battery. Background Art

[0002] As an important energy storage device, lithium-ion batteries have been widely used in electric vehicles, mobile devices, energy storage systems and other fields. The safety performance of lithium-ion batteries has always been an important consideration. Once a problem occurs, it may directly affect the battery's service life, performance, and even the safety of the user.

[0003] As a current collector structure, composite foil combines an insulating layer with a metal conductive layer to form a sandwich structure. Compared with traditional pure metal current collectors, composite foil has the advantage of improving the safety of lithium-ion batteries, and to a certain extent improves the energy density of lithium-ion batteries and reduces costs. Traditional laminated lithium-ion batteries with composite foil as current collectors usually roll-weld metal foil on both sides of each layer of tabs to achieve conduction of multiple layers of electrode sheets. However, this will cause the thickness of the tab welding to be too large, making the composite foil difficult to apply to laminated soft-pack batteries with high space requirements. Utility Model Content

[0004] The purpose of the utility model is to solve at least one of the technical problems existing in the prior art and to provide a laminated composite current collector soft-package electrode group and a battery. The laminated composite current collector soft-package electrode group can not only realize the conduction of the metal layers on both sides of the insulating layer of the laminated multi-layer composite foil, but also reduce the thickness of the electrode ear welding.

[0005] In order to achieve the above-mentioned object, the utility model provides, on one hand, a laminated composite current collector soft-package electrode group, comprising a laminated body formed by alternately stacking a plurality of positive electrode sheets and a plurality of negative electrode sheets, wherein in the thickness direction of the laminated body, the lengths of the positive electrode ears of the plurality of positive electrode sheets gradually increase or gradually decrease, and the lengths of the negative electrode ears of the plurality of negative electrode sheets gradually increase or gradually decrease;

[0006] The positive electrode sheet uses a composite aluminum foil as a base material, and the negative electrode sheet uses a composite copper foil as a base material;

[0007] The positive electrode tabs of multiple different lengths are flattened along the thickness direction of the stacked body to form an L-shaped positive electrode tab stacked body, and the negative electrode tabs of multiple different lengths are flattened along the thickness direction of the stacked body to form an L-shaped negative electrode tab stacked body;

[0008] The L-shaped positive electrode tab stack is welded to the aluminum foil, and the L-shaped negative electrode tab stack is welded to the copper foil.

[0009] Preferably, the difference in length between the positive electrode tabs on two adjacent positive electrode sheets is equal; and / or the difference in length between the negative electrode tabs on two adjacent negative electrode sheets is equal.

[0010] Preferably, the difference in length between the positive electrode ears on two adjacent positive electrode sheets is 0.5-3 mm, and the difference in length between the negative electrode ears on two adjacent negative electrode sheets is 0.5-3 mm.

[0011] Preferably, the length of the plurality of positive electrode tabs is 2-12 mm; and / or the length of the plurality of negative electrode tabs is 2-12 mm.

[0012] Preferably, the composite aluminum foil comprises an insulating layer of 2 to 10 μm, and metal aluminum layers of 1 to 2 μm are respectively provided on both sides of the insulating layer. The thickness of the composite aluminum foil is 4 to 12 μm.

[0013] Preferably, the composite copper foil comprises an insulating layer of 2 to 8 μm, and metal copper layers of 1 to 2 μm are respectively arranged on both sides of the insulating layer. The thickness of the composite copper foil is 4 to 10 μm.

[0014] Preferably, the thickness of the aluminum foil is 12-16 μm.

[0015] Preferably, the copper foil has a thickness of 6-10 μm.

[0016] Preferably, the plurality of positive electrode tabs have the same width, which is 5-20 mm; and / or the plurality of negative electrode tabs have the same width, which is 5-20 mm.

[0017] A second aspect of the present invention provides a battery, wherein the battery has any one of the laminated composite current collector soft-package electrode groups described above.

[0018] Through the above technical scheme, the positive electrode sheet of the laminated composite current collector soft-package electrode group uses a composite aluminum foil as a substrate, and the negative electrode sheet uses a composite copper foil as a substrate, which improves the energy density and safety performance of the lithium-ion battery to a certain extent. By flattening a plurality of positive electrode ears of different lengths and a plurality of negative electrode ears of different lengths along the thickness direction of the laminate to form an L-shaped positive electrode ear laminate and an L-shaped negative electrode ear laminate, and then welding the aluminum foil to the L-shaped positive electrode ear laminate, and the copper foil to the L-shaped negative electrode ear laminate, multi-layer conduction of the composite foil is achieved, and the problem of excessive thickness of the welding point caused by double-sided rolling welding of metal foil on each layer of the composite foil is effectively solved. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a schematic diagram of the front view and side view of the stacked body of a laminated composite current collector soft-package electrode group provided by the utility model;

[0020] Figure 2It is a front view structural diagram of the positive electrode sheet in the utility model;

[0021] Figure 3 It is a front view structural schematic diagram of the negative electrode sheet in the utility model;

[0022] Figure 4 It is a schematic diagram of the structure of the L-shaped negative electrode ear stack in the utility model;

[0023] Figure 5 It is a schematic diagram of welding an L-shaped positive electrode tab stack and an aluminum foil, and a schematic diagram of welding an L-shaped negative electrode tab stack and a copper foil in the utility model;

[0024] Figure 6 It is a schematic diagram of a transfer welding part for transfer welding of two groups of L-shaped negative pole ear stacked bodies and external pole ear transfer welding in the utility model.

[0025] Description of Reference Numerals

[0026] 1. Positive electrode sheet; 11. Positive electrode ear; 2. Negative electrode sheet; 21. Negative electrode ear; 3. Aluminum foil; 4. Copper foil; 5. Welding stamp; 6. External electrode ear transfer welding parts. DETAILED DESCRIPTION

[0027] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0028] It should be noted that, in the description of the present utility model, words such as “include” or “comprises” and the like mean that the elements before the word include the elements listed after the word, and do not exclude the possibility of also including other elements.

[0029] Combination Figure 1 , Figure 2 as well as Figure 3 As shown, the utility model provides a laminated composite current collector soft-package electrode group, including a stacked body formed by alternately stacking a plurality of positive electrode sheets 1 and a plurality of negative electrode sheets 2, in the thickness direction of the stacked body, the length of the positive electrode ears 11 of the plurality of positive electrode sheets 1 gradually increases or gradually decreases, and the length of the negative electrode ears 21 of the plurality of negative electrode sheets 2 gradually increases or gradually decreases, the positive electrode sheet 1 uses a composite aluminum foil as a substrate, and the negative electrode sheet 2 uses a composite copper foil as a substrate, which improves the energy density and safety performance of the lithium-ion battery to a certain extent, wherein the positive electrode sheet 1 also includes a positive electrode coating coated on the composite aluminum foil, and the negative electrode sheet 2 also includes a negative electrode coating coated on the composite copper foil, the positive electrode coating includes 95-98wt% of positive electrode active material, 1-3wt% of conductive agent and 1-3wt% of binder, and the negative electrode coating includes 95-98wt% of negative electrode active material, 1-3wt% of conductive agent and 1-3wt% of binder.

[0030] The positive electrode ears 11 of multiple different lengths are flattened along the thickness direction of the stack to form an L-shaped positive electrode ear stack, and the negative electrode ears 21 of multiple different lengths are flattened along the thickness direction of the stack to form an L-shaped negative electrode ear stack. The L-shaped positive electrode ear stack is welded to the aluminum foil 3, and the L-shaped negative electrode ear stack is welded to the copper foil 4. Figure 5 As shown, multi-layer conduction of the composite foil is achieved, and the problem of excessive thickness of the welding point caused by double-sided roll welding of metal foil on each layer of the composite foil tab is effectively solved.

[0031] It can be understood that the L-shaped tab stack is conducive to the tabs of the stack being closely stacked in the vertical direction, thereby effectively saving space. By arranging two sets of stacks in the laminated composite current collector soft-pack electrode group, the L-shaped tab stacks of the two sets of stacks are back-to-back and then welded to the external tab welding piece 6, as shown in FIG. Figure 6 As shown, the design of external connection can be simplified. In this way, when welding the external tab welding piece 6, only the connection between the two groups of laminated bodies needs to be processed, and the tabs of each group of laminated bodies need not be processed separately, thereby reducing the number and complexity of the connectors. This compact design helps to increase the energy density of the battery, allowing the soft-pack battery to accommodate more battery capacity in a limited space.

[0032] Furthermore, the difference in length of the positive electrode ears 11 on two adjacent positive electrode sheets 1 and the difference in length of the negative electrode ears 21 on two adjacent negative electrode sheets 2 may be equal or unequal. Preferably, the difference in length of the positive electrode ears 11 on two adjacent positive electrode sheets 1 is equal; and / or the difference in length of the negative electrode ears 21 on two adjacent negative electrode sheets 2 is equal.

[0033] Specifically, the difference in length between the positive electrode tabs 11 on two adjacent positive electrode sheets 1 is 0.5-3 mm, and the difference in length between the negative electrode tabs 21 on two adjacent negative electrode sheets 2 is 0.5-3 mm.

[0034] Preferably, the lengths of the exposed positive and negative tabs 11 and 21 in the stack are both 2-12 mm. Compared with the tabs of different lengths in the stack, the shortest tab is preferably 2-6 mm long, and the longest tab is less than 12 mm long.

[0035] Preferably, the plurality of positive electrode tabs 11 have the same width, which is 5-20 mm, and / or the plurality of negative electrode tabs 21 have the same width, which is 5-20 mm.

[0036] In the utility model, the composite aluminum foil comprises an insulating layer of 2 to 10 μm, and a 1 to 2 μm metal aluminum layer is evaporated on both sides of the insulating layer. The thickness of the composite aluminum foil is 4 to 12 μm, and the surface density is 11 to 18 g / m 2The composite copper foil includes an insulating layer of 2 to 8 μm, and a metal copper layer of 1 to 2 μm is sputtered on both sides of the insulating layer. The composite copper foil has a thickness of 4 to 10 μm and a surface density of 20 to 27 g / m 2 The composite copper / aluminum foil intermediate insulating layer is made of one or more of PET, PP or PEN.

[0037] In the present invention, the thickness of the aluminum foil 3 is preferably 12-16 μm, wherein the Al content is ≥99.3%, and the thickness of the copper foil 4 is preferably 6-10 μm, wherein the Cu content is ≥99.8%.

[0038] The present invention is further described below in conjunction with specific embodiments. The following embodiments are preferred embodiments of the present invention and cannot limit the claims of the present invention. The present invention has many other implementation methods. Any technical solutions formed by equivalent replacement or equivalent transformation are within the scope of protection required by the present invention.

[0039] Embodiment 1

[0040] This embodiment provides a method for manufacturing a lithium battery soft-pack laminated battery, wherein the positive electrode sheet 1 obtained according to steps M1.1-M1.5 and the negative electrode sheet 2 obtained according to steps M2.1-M2.5 are prepared into a soft-pack electrode group, comprising the following steps:

[0041] M3.1. Take a group of positive electrode sheet 1 and negative electrode sheet 2 respectively, and stack the positive and negative electrode sheets in order from short to long according to the length of the electrode ears. The positive electrode sheet 1, negative electrode sheet 2 and separator are stacked in the order of separator-negative electrode sheet 2-separator-positive electrode sheet 1-separator to form a stacked body. The positive electrode ear 11 of this stacked body is located on the left, and the negative electrode ear 21 is located on the right, such as Figure 1 shown.

[0042] M3.2, the negative electrode ear 21 is as follows Figure 4 As shown in the figure, the stack is flattened in the thickness direction to form an L-shaped negative electrode tab stack, and a 16 mm wide copper foil 4 is overlapped on both sides AB of the L-shaped negative electrode tab stack, and then the two sides of the copper foil 4 are roll welded as shown in the figure. Figure 5 , the welding width is 3mm, and the positive electrode ear 11 is also flattened and roll-welded according to the above steps, wherein the thickness of the aluminum foil is 12μm, and the thickness of the copper foil is 6μm. This soft-package electrode group prototype is called A1.

[0043] M3.3. Another set of positive electrode sheet 1 and negative electrode sheet 2 is also operated according to the steps described in M3.1 and M3.2. The positive electrode ear 11 of this stacked body is located on the right, and the negative electrode ear 21 is located on the left. This soft-package electrode group is initially called A2.

[0044] M3.4, stack A1 and A2 together, and transfer the two groups of welded L-shaped positive tab stacks and the two groups of welded L-shaped negative tab stacks to the external tab welding parts 6, such as Figure 6 The final electrode group obtained at this time is called T.

[0045] M3.5. The final electrode group T obtained in M3.4 is packaged with aluminum-plastic film, injected with liquid, aged, formed, finally sealed and divided into different capacities to complete the battery production.

[0046] The steps for making the positive electrode sheet 1 are as follows:

[0047] M1.1. The positive electrode coating consists of 96.5wt% of lithium nickel cobalt manganese oxide (NCM), 1.5wt% of a conductive agent and 2wt% of PVDF.

[0048] M1.2. Add PVDF to NMP and stir at high speed for 2.5 hours to obtain glue with a solid content of 8wt%. Then add the conductive agent and the positive electrode active material to the glue in sequence. After stirring for 4.5 hours, use NMP to adjust the slurry viscosity to 5500mPa.S and the solid content to 72wt% to obtain the positive electrode slurry.

[0049] M1.3. The positive electrode slurry is passed through a 200-mesh sieve and then coated on an 8-μm composite aluminum foil. The coating surface density is 172±3.4 g / cm 2 The coating is double-sided gap coating (coating length 218±1mm, blank length 50±1mm). After drying, the pole piece is rolled to a thickness of 112±2μm and a compaction density of 3.3g / cm 2 .

[0050] M1.4. Place the rolled pole piece according to Figure 2 Punch the sheets according to the size, punch 20 sheets, Figure 2 The length of the shaded portion is 104±0.5 mm, and the width is 73±0.5 mm. The length of the ear area above the shaded portion is 20±0.5 mm, and the width is 20±0.5 mm. The shortest vertical distance from the long side of the ear area to the long side of the shaded portion is 10.5±0.5 mm.

[0051] M1.5. Cut the positive electrode sheet 1 obtained in M1.4 to the length of the tab, with 10 sheets in a group, for a total of two groups. The shortest positive tab 11 is 3.25 mm, and increases with a tolerance of 0.75 mm. The longest positive tab 11 is 10 mm.

[0052] The steps for making the negative electrode sheet 2 are as follows:

[0053] M2.1. The negative electrode coating consists of 95.5wt% graphite, 1.5wt% conductive agent and 3wt% PVDF.

[0054] M2.2. Add PVDF to NMP and stir at high speed for 2.5 hours to obtain glue with a solid content of 8wt%. Then add the conductive agent and the negative electrode active material to the glue in sequence. After stirring for 4.5 hours, use NMP to adjust the slurry viscosity to 3670mPa.S and the solid content to 50wt% to obtain the negative electrode slurry.

[0055] M2.3. The negative electrode slurry was passed through a 200-mesh screen and then coated on a 6.5 μm composite copper foil. The coating surface density was 80.5 ± 1.6 g / cm 2 The coating is double-sided gap coating (coating length 222±1mm, blank length 50±1mm). After drying, the pole piece is rolled to a thickness of 110±2μm and a compaction density of 1.55g / cm 2 .

[0056] M2.4, roll the rolled negative electrode sheet 2 according to Figure 3 Punch the sheets according to the size, 22 sheets are punched. Figure 3 The length of the shaded portion is 106±0.5mm, and the width is 75±0.5mm. The length of the ear area above the shaded portion is 20±0.5mm, and the width is 20±0.5mm. The shortest vertical distance from the long side of the ear area to the long side of the shaded portion is 11.5±0.5mm.

[0057] M2.5. Cut the negative electrode sheets 2 obtained in M2.4 to the length of the tabs, with 11 sheets in a group, for a total of two groups. The shortest negative electrode tab 21 is 3.25 mm, and increases with a tolerance of 0.75 mm. The longest negative electrode tab 21 is 10.75 mm.

[0058] Comparative Example 1

[0059] This comparative example provides a lithium battery soft-pack laminated battery, whose positive and negative electrodes are different from those in Example 1. Specifically, the positive electrode is prepared by coating the positive electrode slurry on a 12μm aluminum foil, and the negative electrode is prepared by coating the negative electrode slurry on a 6μm copper foil. The length of the positive and negative electrode tabs is 5mm. The external tabs are directly ultrasonically welded after lamination. The remaining steps are the same.

[0060] The performance of the lithium battery soft-pack laminated battery provided in Example 1 and Comparative Example 1 of the present invention was evaluated according to the following test items.

[0061] 1. Normal temperature capacity (mAh): At an ambient temperature of 20℃±5℃, charge the fully discharged battery at a constant current of 0.2C to 4.2V, then switch to constant voltage charging with a cut-off current of 0.05C. After leaving it for 1h, discharge the battery at a constant current of 0.2C to a cut-off of 2.5V, and record the discharge capacity (mAh) of the battery.

[0062] 2. Energy density (Wh / kg): At an ambient temperature of 20℃±5℃, record the battery energy (Wh) according to the above-mentioned normal temperature capacity test method, and weigh the battery weight (g). According to the calculation formula, energy density (Wh / kg) = energy (Wh) ÷ battery weight (g) × 1000, the energy density value is obtained.

[0063] 3. Short circuit: At an ambient temperature of 20℃±5℃, the fully charged battery is tested after 8 hours. A wire with a resistance value of less than 50mΩ is used to short-circuit the positive and negative poles of the battery. The short circuit time is 24 hours or the battery temperature drops to 20% lower than the peak value. The battery under test is required not to catch fire, deflagrate or explode during the test.

[0064] 4. Heavy impact: Under normal temperature conditions, place a fully charged battery on a flat plate. The longitudinal axis of the battery should be parallel to the flat plate and perpendicular to the longitudinal axis of the steel rod placed in the center of the sample. A steel rod with a diameter of 15.8mm±0.2mm is placed horizontally in the center of the battery. The surface of the flat plate and the steel rod is insulated. The longitudinal axis of the steel rod is parallel to the plane. A 9.1kg±0.1kg weight is allowed to fall freely from a height of 610mm±25mm onto the steel rod above the center of the battery. The battery is impacted in two axial directions perpendicular to the longitudinal axis of the battery. Each battery under test can only be subjected to one heavy object impact test. After the heavy object impact, continue to observe the battery under test for 6 hours. The battery under test should not catch fire, deflagrate, or explode during the test and observation period.

[0065] 5. Acupuncture: Under normal temperature conditions, for fully charged batteries, use a high-temperature resistant steel needle with a diameter of 3mm. The cone angle of the needle tip is 45°~60°. The surface of the needle is smooth, free of rust, oxide layer and oil. Puncture at a speed of (25±5)mm / s. The battery is punctured in the middle of the four sides except the extreme surface and the bottom surface. During the puncture, the device that clamps the steel needle must not touch the battery under test. The steel needle penetrates the shell and stays in the battery under test for 90 minutes, then withdraws the steel needle at a speed of (25±5)mm / s. Continue to observe the battery under test for 6 hours. The battery under test should not catch fire, deflagrate or explode during the test and the observation period. A new steel needle should be replaced for each acupuncture test.

[0066] The test results are summarized in Table 1.

[0067] Table 1

[0068]

[0069] As shown in Table 1, by comparing Example 1 with Comparative Example 1, it can be concluded that the room temperature capacity of Example 1 and Comparative Example 1 is basically the same, and since the density of the composite foil used in Example 1 is smaller than that of the traditional metal foil, its energy density is improved. In addition, from the results of the safety test, under the same test conditions, the short circuit, heavy impact and needle puncture tests of Example 1 all meet the requirements, indicating that the use of the composite foil is conducive to improving the safety performance of the battery.

[0070] The composite foil current collector substrate adopted by the utility model does not affect the performance of the battery capacity, but improves the energy density of the battery to a great extent. More importantly, it has a great improvement on the improvement of safety performance.

[0071] The pole ear welding method adopted by the utility model not only ensures the conduction of the multi-layer current collector, but also solves the problem of excessive thickness of the pole ear caused by double-sided rolling welding of the multi-layer pole ear, and saves the assembly space on the top of the battery, opening up new ideas for the application of composite foil in soft-pack laminated batteries.

Claims

1. A laminated composite current collector soft-package electrode group, characterized in that: A laminated body comprising a plurality of positive electrode sheets (1) and a plurality of negative electrode sheets (2) alternately laminated to form a laminated body, wherein in the thickness direction of the laminated body, the lengths of the positive electrode ears (11) of the plurality of positive electrode sheets (1) gradually increase or gradually decrease, and the lengths of the negative electrode ears (21) of the plurality of negative electrode sheets (2) gradually increase or gradually decrease; The positive electrode sheet (1) uses a composite aluminum foil as a base material, and the negative electrode sheet (2) uses a composite copper foil as a base material; The positive electrode tabs (11) of multiple different lengths are flattened along the thickness direction of the stacked body to form an L-shaped positive electrode tab stacked body, and the negative electrode tabs (21) of multiple different lengths are flattened along the thickness direction of the stacked body to form an L-shaped negative electrode tab stacked body; The L-shaped positive electrode tab stack is welded to the aluminum foil (3), and the L-shaped negative electrode tab stack is welded to the copper foil (4).

2. The laminated composite current collector soft-package electrode group according to claim 1, characterized in that: The difference in length between the positive electrode ears (11) on two adjacent positive electrode sheets (1) is equal; and / or The difference in length between the negative electrode ears (21) on two adjacent negative electrode sheets (2) is equal.

3. The laminated composite current collector soft-package electrode group according to claim 2, characterized in that: The difference in length between the positive electrode ears (11) on two adjacent positive electrode sheets (1) is 0.5-3 mm, and the difference in length between the negative electrode ears (21) on two adjacent negative electrode sheets (2) is 0.5-3 mm.

4. The laminated composite current collector soft-package electrode group according to claim 3, characterized in that: The length of the plurality of positive electrode tabs (11) is 2-12 mm; and / or The length of the plurality of negative electrode ears (21) is 2-12 mm.

5. The laminated composite current collector soft-package electrode group according to claim 1, characterized in that: The composite aluminum foil comprises an insulating layer of 2 to 10 μm, and metal aluminum layers of 1 to 2 μm are respectively arranged on both sides of the insulating layer. The thickness of the composite aluminum foil is 4 to 12 μm.

6. The laminated composite current collector soft-package electrode group according to claim 1, characterized in that: The composite copper foil comprises an insulating layer of 2 to 8 μm, and metal copper layers of 1 to 2 μm are respectively arranged on both sides of the insulating layer. The thickness of the composite copper foil is 4 to 10 μm.

7. The laminated composite current collector soft-package electrode group according to claim 1, characterized in that: The thickness of the aluminum foil (3) is 12 to 16 μm.

8. The laminated composite current collector soft-package electrode group according to claim 1, characterized in that: The copper foil (4) has a thickness of 6 to 10 μm.

9. The laminated composite current collector soft-package electrode group according to claim 1, characterized in that: The widths of the plurality of positive electrode tabs (11) are the same, and are 5-20 mm; and / or The plurality of negative electrode ears (21) have the same width, which is 5-20 mm.

10. A battery, characterized in that: The battery has the laminated composite current collector soft-package electrode group according to any one of claims 1 to 9.